Raman spectroscopy and X‐ray diffraction responses when measuring health‐related micrometre and nanometre particle size fractions of crystalline quartz and the measurement of quartz in dust samples from the cutting and polishing of natural and artificial stones. (3rd May 2021) - Stacey, Peter; Hall, Samantha; Stagg, Stephen; Clegg, Francis; Sammon, Christopher
Abstract: Around 560 000 workers in Great Britain are potentially exposed to respirable crystalline silica (RCS), which can cause disabling diseases, such as silicosis and lung cancer. These experiments assessed the performance of a new Raman spectroscopy method for measuring RCS, in samples of pure quartz powder with different median aerodynamic particle diameters and stone dusts from variety of natural and artificial stones. The relationship between the Raman response and particle size was characterised by measuring subfractions of the respirable quartz standard A9950 collected using the Sioutas impactor. Bulk samples of quartz standards A9950 and Quin B that provided the highest median particle size diameters were also measured. Health‐related thoracic and respirable particle size fractions, and the environmental monitoring fractions of PM10, PM2.5, PM1 and PM0.5, were also collected during the powered cutting and polishing of sandstone and diorite (granite), engineered and sintered stones. All Raman spectroscopy results were compared with those from X‐ray diffraction (XRD), which was used as the reference technique. The Raman spectroscopy response closely followed the predicted crystallinity of RCS for different particle diameters. Raman spectroscopy obtained slightly higher percentages than XRD for particle size fractions below 1 μm. The Raman spectroscopy and XRD results were highly correlated for the thoracic, respirable and impactor fractions. The coefficients of determination were between 0.98 and 0.95. The slope coefficients for the correlation were 1.11 for the respirable fraction and 1.07 for the thoracic fraction. Raman spectroscopy is a promising alternative to XRD for measurement of RCS with a much lower limit of detection of 0.21 μg compared with 1 μg. Abstract : Raman spectroscopy is an emerging technique to assess people's exposure to respirable crystalline silica. We characterised the Raman band response at 464 cm −1 when measuring the respirable ( d 50 = 4 μm), thoracic ( d 50 = 10 μm) and environmental particle size fractions of PM10, PM2.5, PM1 and PM0.5. We also demonstrate the advantages of Raman spectroscopy over X‐ray diffraction analysis when measuring emissions from engineered, sintered, and diorite stones and sandstone.